Śrīmadbhāgavata daśamaskandha va tyāvarīla Śivakalyāṇāñcī prākrta ṭīkā : Rāsapañcādhyāyī - Śivakalyāṅa (Gaṇeśa Balavanta Moḍaka, 1904)
On Rāsapañcādhyāyī from the Bhāgavatapurāṇa, expounding the erotic sports of Krishna, Hindu deity.